PLANT REGENERATION THROUGH PROTOCORM-LIKE BODIES DERIVED FROM STEM THIN LAYER OF Anubias barteri var. Nana Petite - Giang K. T. Le; Tinh V. Nguyen; Ngan K. T Tran; Vy T. H. Dang; Phong V. Nguyen (SEAMEO BIOTROP, 2024)
Article Highlights- Effective induction of PLBs from stem thin layer and shoot regeneration using specific BAP and auxin combinations.- Significant role of potato extract in enhancing shoot regeneration.- Highest shoot regeneration rate achieved with 3 mg/L BAP concentration. AbstractAnubias barteri var. nana Petite, a highly valued ornamental aquatic plant in the Araceae family, faces challenges in vegetative propagation due to its slow multiplication rate. This study established a robust micropropagation protocol for rapid and efficient multiplication of A. barteri var. nana Petite. Explants were subjected to thorough sterilization, and shoot induction and multiplication were optimized using varying concentrations of Benzyl adenine (BA) on Murashige and Skoog (MS) medium. Protocorm-like bodies (PLBs) were induced from transverse thin-layer explants using combinations of BAP and Naphthaleneacetic acid (NAA). PLB multiplication and shoot regeneration were achieved through a sequential culture protocol. In addition, the influence of potato extract on shoot regeneration and the role of Indole-3-butyric Acid (IBA) in root development were explored. This study demonstrated a 100% survival rate of regenerated shoots in aquariums. Ongoing research is focused on further enhancing PLB multiplication. This optimized micropropagation protocol holds promise for the large-scale production of A. barteri var. nana Petite, addressing the limitations of natural propagation.